Influence of Good Governance on ASEAN Economic Growth - Andesta, Herma Yola; Gunarto, Toto; Aida, Neli (FEB - Universitas Lampung, 2022)
Economic growth is the process of changing the economic conditions of a country on an ongoing basis towards a better state, namely an increase in the physical production of goods and services prevailing in a country. The success of the performance of the government and its institutions and agencies related to the economy is measured by the resulting economic growth. Therefore, economic growth becomes important in assessing the success of a country in achieving its economic development over a certain period. This study aims to analyze the influence of the government on economic growth. The research was conducted in ASEAN countries with 5 categories of countries with the highest level of voice and accountability. The data used is secondary data from 2009-2019. The analytical tool used in this research is the Fixed Effect Model. Based on the results of data processing and discussions that have been carried out, it can be concluded that Voice and Accountability, Political Stability, Rule of Law, Foreign Direct Investment, Manpower and Initial Growth have a positive and significant impact on economic growth in 10 ASEAN countries in 2009-2019.